Решить уравнения: 1.(х-3)(х²+3х+9)-х(х²-16)=21 2.(2х-1)(4х²+2х+1)=23+4х(2х²-3) 3.16х(4х²-5)+17=(4х+1)(16х²-4х+1)

AndreevaAS2 AndreevaAS2    3   16.07.2019 12:20    0

Ответы
Emmaasakura Emmaasakura  21.09.2020 10:29
1)(x-3)(x²+3x+9)-x(x²-16)=21
x^3+3x²+9x-3x²-9x-27-x^3+16x-21=0
16x-48=0
16x=48
x=48/16
x=3
2)(2x-1)(4x²+2x+1)=23+4x(2x²-3)
8x^3+4x²+2x-4x²-2x-1=23+8x^3-12x
24-12x=0
12x=-24
x=-24/12
x=-2
3)16x(4x²-5)+17=(4x+1)(16x²-4x+1)
64x^3-80x+17=64x^3-16x²+4х+16x²-4x+1
-80x+16=0
-80x=16
x=16/-80
x=-0.2
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра